2013
DOI: 10.4236/as.2013.46041
|View full text |Cite
|
Sign up to set email alerts
|

Larvae of mealworm (<i>Tenebrio molitor</i> L.) as European novel food

Abstract: For centuries, insects have been used as food due to their availability and easiness in raising that is much less burdensome for environment than animal husbandry breeding. Mealworm (Tenebrio molitor L.) is a store-pest of which larvae are consumed by people. The aim of the work was to determine the nutritional value of larvae of mealworm (Tenebrio molitor L.). The material was a three-month-old mealworm larva 25 -30 mm in length. Larvae were boiled for 3 min and next dried in 60˚C. Contents of water, ash, min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
78
3
7

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(114 citation statements)
references
References 12 publications
(19 reference statements)
13
78
3
7
Order By: Relevance
“…The interest in insects comes from their very high efficiency in transforming phytomass into protein-rich animal biomass, their high fecundity, their very fast growth rates, and also their ability to absorb all the water they need from just their food [37,38,41]. It has also been reported that mealworms do not need any additional drinking water if they are farmed in appropriate humidity conditions and provided with carrots and the appropriate ratio of bran/grains [42].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The interest in insects comes from their very high efficiency in transforming phytomass into protein-rich animal biomass, their high fecundity, their very fast growth rates, and also their ability to absorb all the water they need from just their food [37,38,41]. It has also been reported that mealworms do not need any additional drinking water if they are farmed in appropriate humidity conditions and provided with carrots and the appropriate ratio of bran/grains [42].…”
Section: Discussionmentioning
confidence: 99%
“…This result, divided by the output of livestock production amounted to 83.2 t of mealworms as extracted from Oonincx and de Boer [22] and shown in Table 1, gives rise to the water footprint for the production of mealworms, which is equal to 4341 m 3 /t, as indicated in Table 4. If we compare the average total annual water footprint per animal (WFfeed + WFdrink + WFserv) of different animal categories (Table 5), we find that beef cattle have the largest (631 m [38]. ** Calculated as the average time in which Tenebrio molitor and Zophobas morio reach adulthood based on Oonincx and de Boer data [22].…”
Section: Crops Roughages and Crop By-productsmentioning
confidence: 99%
“…Now a day, it is studied as a potential human novel-food. 13 The worm not only eats stored food, but also contaminates it with exuviates excrements and dead insects. T. Molitor L. is omnivorous and originates generally from damp, dark places where cereals may be decaying.…”
Section: Discussionmentioning
confidence: 99%
“…The larvae samples were placed in 40 × 28 × 24 cm plastic aquariums and fed with oats and cucumbers as a food source during the rearing process (Siemianowska et al, 2013). Some parameters, including temperature, humidity, and CO 2 concentration were recorded.…”
Section: Rearing Process Of Tenebrio Molitormentioning
confidence: 99%